2002
DOI: 10.1118/1.1500403
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of dark current radiation in step‐and‐shoot intensity modulated radiation therapy by the initial pulse‐forming network

Abstract: The effect of the initial pulse forming network (IPFN) on the suppression of dark current is investigated for a Siemens Primus accelerator. The dark current produces a spurious radiation, which is referred to as dark current radiation (DCR) in this study. In the step-and-shoot delivery of an intensity modulated radiation therapy (IMRT), the DCR could be of some concern for whole body dose along with leakage radiation through collimator jaws or multileaf collimator. By adjusting the IPFN-to-PFN ratio to >0.8, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…13 The intensity modulated (IM) mode, with which Siemens linacs regulate beam delivery for stepand-shoot IMRT, is unique. 14,15 In IM mode, the Artiste TM accelerator does not switch off between subfield deliveries, but the injector that feeds electrons to the waveguide is desynchronized from the radio-frequency (RF) pulse. To evaluate the characteristics of low-MU beams for use in IMRT, beams produced in IM mode were measured.…”
Section: A Linear Accelerator and Irradiationmentioning
confidence: 99%
“…13 The intensity modulated (IM) mode, with which Siemens linacs regulate beam delivery for stepand-shoot IMRT, is unique. 14,15 In IM mode, the Artiste TM accelerator does not switch off between subfield deliveries, but the injector that feeds electrons to the waveguide is desynchronized from the radio-frequency (RF) pulse. To evaluate the characteristics of low-MU beams for use in IMRT, beams produced in IM mode were measured.…”
Section: A Linear Accelerator and Irradiationmentioning
confidence: 99%
“…During the beam hold-off of the step-and-shoot IMRT the IPFN ͑Initial Pulse Forming Network͒ signal is detuned to prevent any dark current generation. 26 IPFN is not detuned during the beam hold-off of the gating on the Siemens Primus accelerator. Therefore, the dark current for the beam hold during gating may be higher than that for the beam hold during the step-and-shoot IMRT.…”
Section: Dark Current Radiationmentioning
confidence: 99%
“…7 With a different beam switching mechanism, it should be of concern whether the dose delivered is linear, reproducible, and uniform. [8][9][10] The recent work of Cheng and Das 9,10 indicated that the dose is nonlinear for small monitor units. Using film dosimetry, they also indicated that the dose is not reproducible and nonuniform.…”
Section: Introductionmentioning
confidence: 99%